2012
DOI: 10.1159/000337777
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Numbers of Cells Producing Interleukin-5 and Interleukin-10 in a Boy with Kimura Disease

Abstract: Kimura disease is a rare disorder of unknown etiology, characterized by the presence of benign subcutaneous granuloma, marked peripheral blood eosinophilia and elevation of the immunglobulin E (IgE) serum level. Here, we present a case of a 12-year-old boy with Kimura disease who had a history of repeated severe influenza virus A infection. Along with the characteristic histological findings of granuloma, including eosinophil infiltration, enzyme-linked immunospot assay showed elevated numbers of IL-5- and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In our study, dermatologists diagnosed most patients, a fact that may account for the larger number of dermatological past conditions reported. These cutaneous manifestations may result from a physiopathological process similar to KD, characterized by a predominant expression of Th2 cytokines, stimulating eosinophils and IgE production [10,22] as in atopic dermatitis. The history of unspecific dermatitis was not associated with recurrence in our study though it appeared more frequently in patients with recurrence (69%) than in patients without (33%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, dermatologists diagnosed most patients, a fact that may account for the larger number of dermatological past conditions reported. These cutaneous manifestations may result from a physiopathological process similar to KD, characterized by a predominant expression of Th2 cytokines, stimulating eosinophils and IgE production [10,22] as in atopic dermatitis. The history of unspecific dermatitis was not associated with recurrence in our study though it appeared more frequently in patients with recurrence (69%) than in patients without (33%).…”
Section: Discussionmentioning
confidence: 99%
“…Association between Kimura's disease and renal involvement remains unclear. Previous studies suggest that the predominance of Th2 and Tc1 cells and certain cytokines including IL-5 as an eosinophil-active cytokine and IL-10 may contributes to the pathogenesis of Kimura's disease, but further research is warranted [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…12 Additional studies have shown elevated granulocyte-macrophage stimulating-factor (GM-CSF), tumor necrosis factor-α (TNF-α), soluble interleukin (IL)-2 receptor (sIL-2R), IL-4, IL-5, IL-10, and IL-13. 13,14 Another study indicated that the activation of the IL-21/pERK1/2 pathway is a component of Kimura disease immunopathogenesis and pERK1/2 could be a potential prognostic indicator of the disease. 15 These findings may help lay the groundwork for elucidating the underlying pathophysiology of Kimura disease.…”
Section: Discussionmentioning
confidence: 99%